The Impact of Clinical Review Bias on Child Language Grammaticality. (August 2020) - Castilla-Earls, Anny P.; Harvey, Brittany; Fulcher-Rood, Katrina; Barr, Christopher D.
The purpose of this study was to examine the impact of clinical review bias on the coding of grammaticality in child language. Seventy-four native-English students studying communication disorders and sciences made judgments about the grammaticality of 250 utterances presented in five language samples. Each language sample included grammatical, ungrammatical, and ambiguous utterances. Participants were randomly assigned to a blind or nonblind group. The nonblind group was presented with diagnostic information, whereas the blind group was not. We employed a generalized linear mixed model to examine the binary data. Our results suggest that both blind and nonblind participants were accurate in judging grammatical and ungrammatical utterances. However, nonblind participants were slightly more likely to judge ambiguous utterances as ungrammatical when the language sample identified the child as having a language impairment, suggesting that there was an effect of clinical review bias in this study. This effect, although statistically significant, was small.